PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA ANTARA DEBITOR DAN KREDITOR (Studi Kasus Ace Hardware) - Dinda Putri Oktaviansjah (2022)
The impact of failure to fulfill agreements related to payments is the birth of debt, such as the lawsuit filed by Wibowo & Partners is a lawsuit for Postponement of Debt Payment Obligations (PKPU) which is an opportunity given to debtors to pay off their debts to creditors in a peaceful manner. The research method used in this research is normative juridical with a law approach, a case approach, and a conceptual approach taken through a literature study and analyzed qualitatively using descriptions. The law has provided protection to creditors with Article 1341 of the Civil Code which has been implemented into Articles 41 to 49 of the Bankruptcy Law and Suspension of Debt Payment Obligations (PKPU) in which the Suspension of Debt Payment Obligations is an answer for business continuity.